Erratum: El-Banhawy, E.M. & M. Knapp, M. (2011) Mites of the family Phytoseiidae Berlese from Kenya (Acari: Mesostigmata). Zootaxa, 2945, 1–176. - El-Banhawy, E. M.; M., Knapp M. (Zootaxa, 2011)
(Erratum)